MALARIAL ANTIBODIES AND GLUCOSE-6-PHOSPHATE DEHYDROGENASE (G-6-PD) DEFICIENCY - Gh.H.Edrissian; K.Montazemi; A.R.Nasseri; A.Afshar (Iranian Journal of Public Health, 1983)
The IFA and the blue dye decolourization G6PD tests were applied in three cross-sectional studies to find out were applied in three cross-sectional studies to find out the relationship of malarial antibodies and G6PD deficiency in the male residents of the malarious areas of southern Iran. In the first study that the blood samples were collected in a random sampling method from the whole Hormozgan province, the G6PD deficient individuals has, significantly, lower sero-positive rate (SPR) and also, considerably lower total geometric mean of reciprocal titers (GMRT) with P.falciparum antigen as compared to the G6PD normal subjects. But with P.vivax antigen SPR and GMRT in both groups were almost the same. However in the second and third studies that the blood samples were collected from the selected groups of the residents of the above Hormozgan province with high incidences of malaria no such distinct serological differences between G6PD deficient and G6PD normal groups was observed. It is concluded that the cross-sectional serological survey of malaria in populations who are more frequently exposed to malarial infections, particularly in the areas where P.vivax is also prevalent is not enough to show a conclusive serological evidence to support G6PD /malaria hypotheses.